2021
DOI: 10.3390/pr9060955
|View full text |Cite
|
Sign up to set email alerts
|

Improved Performances of SiBCN Powders Modified Phenolic Resins-Carbon Fiber Composites

Abstract: The effect of SiBCN powder on properties of phenolic resins and composites was analyzed. Compared with phenolic resins, the thermal stability of SiBCN powder modified phenolic resins (the SiBCN phenolic resins) by characterization of thermogravimetric analysis (TGA) improved clearly. It was found by X-ray photoelectron spectroscopy (XPS) that reactions between SiBCN powder and the pyrolysis product of phenolic resins were the main factor of the increased residual weight. TGA and static ablation of a muffle fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The carbon/ceramic network can maintain its structure at high temperatures and resist oxidation due to the presence of the ceramic component. The carbon/ceramic network structure weakens the contact between the fiber and the gas stream, which hinders the pyrolysis of the internal material 56 . Therefore, these carbon fibers exposed to the oxyacetylene flame dissipate a significant amount of incident convective heat through surface radiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The carbon/ceramic network can maintain its structure at high temperatures and resist oxidation due to the presence of the ceramic component. The carbon/ceramic network structure weakens the contact between the fiber and the gas stream, which hinders the pyrolysis of the internal material 56 . Therefore, these carbon fibers exposed to the oxyacetylene flame dissipate a significant amount of incident convective heat through surface radiation.…”
Section: Resultsmentioning
confidence: 99%
“…The carbon/ ceramic network structure weakens the contact between the fiber and the gas stream, which hinders the pyrolysis of the internal material. 56 Therefore, these carbon fibers exposed to the oxyacetylene flame dissipate a significant amount of incident convective heat through surface radiation. In the carbonization layer, the aerogel around the fibers has larger pores and sparser networks than the original layer, which is caused by the carbonization of PSZ-PRAs.…”
Section: Ablation Performance Of Psz-pr/ Cf Compositesmentioning
confidence: 99%
“…To address these challenges, many works have been carried out, such as the introduction of B-based ceramics, 12,13 Si-based ceramics, 14,15 Zr-based ceramics 16,17 into PR, many studies have shown that the introduction of ceramics prevents the oxidation of residue char, as a high temperature resistant ceramic coating can be formed during the ablation. However, in the actual manufacturing process, there are certain manufacturing difficulties due to the difference in density between the filler and the resin matrix.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of these is expected to enhance their performance under extreme circumstances. 10,16,17 Typically, multiphase ceramics with metals are commonly employed as aeronautical materials, due to their excellent performance under extreme thermal shock. 18–23 …”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of these is expected to enhance their performance under extreme circumstances. 10,16,17 Typically, multiphase ceramics with metals are commonly employed as aeronautical materials, due to their excellent performance under extreme thermal shock. [18][19][20][21][22][23] In spite of the promising property of multiphase ceramics, [24][25][26] the improvement mechanisms on mechanical properties of metal-SiBCN remain unclear.…”
Section: Introductionmentioning
confidence: 99%